Different sequelae of electrical brain injury — MRI patterns. Issue 4 (June 2017) - Grassner, Lukas; Bierschneider, Michael; Strowitzki, Martin; Grillhösl, Andreas
Highlights: In electrical injury prompt cranial computed tomography is indicated to rule out event-associated injuries, for example intracranial hemorrhage. In prolonged unconscious patients MR-imaging should be performed to detect the extent of brain damage for therapeutic and prognostic reasons. Moreover MRI is best suited for differentiating hypoxic, thermal and nonthermal mechanisms of electric injury contributing to the cerebral damage. Abstract: Purpose: Electrical injury to the central nervous system may lead to neurologic compromise via pleiotropic mechanisms. It may cause current-related, thermal or nonthermal damage followed by secondary mechanisms. Methods: We herein report a case of a 20-year old man, who experienced a low-voltage electric injury due to an occupational accident. Results: Magnetic resonance imaging (MRI) one week after the insult allowed differentiation of pathophysiologic features including thermal, nonthermal and hypoxic cerebral lesions. Conclusion: The capability of MRI assessing a variety of lesions for diagnostic and potentially prognostic reasons is presented.